2017
DOI: 10.3168/jds.2016-12459
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hepatic genes related to energy metabolism during the transition period of Holstein and F1 Holstein-Gir cows

Abstract: The aim of this study was to investigate the expression of genes encoding enzymes and other factors involved with carbohydrate and lipid metabolism in the liver of 2 genetic groups of dairy cows during the transition period. We analyzed the expression of glucose-6-phosphatase (G6PC), cytosolic phosphoenolpyruvate carboxykinase (PEPCK-C), methylmalonyl-CoA mutase (MUT), β-hydroxybutyrate dehydrogenase-2 (BDH2), acetyl-CoA carboxylase (ACC), carnitine palmitoyltransferase-2 (CPT2), 3-hydroxy-3-methylglutaryl-CoA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…In another examination, Laguna et al [ 87 ] examined the expression of genes that encode for the enzymes and different processes linked with the metabolism of lipids and carbohydrates of 2 genetic classes of dairy cows in the transition phase. Examination of the expression of cytosolic phosphoenolpyruvate carboxykinase ( PEPCK-C ), glucose-6-phosphatase (G6PC), β -hydroxybutyrate dehydrogenase-2 ( BDH2 ), methylmalonyl-CoA mutase ( MUT ), carnitine palmitoyltransferase-2 ( CPT2 ), acetyl-CoA carboxylase ( ACC ), glucose transporter-2 ( SLC2A2 ), 3-hydroxy-3-methylglutaryl-CoA reductase ( HMGCR ), and the transcription factor peroxisome proliferator-activated receptor α ( PPARA ) was directed, and a comparison was established between Holstein and F1 Holstein-Gir cows.…”
Section: Strategies To Alleviate Biological Stress During the Transit...mentioning
confidence: 99%
See 1 more Smart Citation
“…In another examination, Laguna et al [ 87 ] examined the expression of genes that encode for the enzymes and different processes linked with the metabolism of lipids and carbohydrates of 2 genetic classes of dairy cows in the transition phase. Examination of the expression of cytosolic phosphoenolpyruvate carboxykinase ( PEPCK-C ), glucose-6-phosphatase (G6PC), β -hydroxybutyrate dehydrogenase-2 ( BDH2 ), methylmalonyl-CoA mutase ( MUT ), carnitine palmitoyltransferase-2 ( CPT2 ), acetyl-CoA carboxylase ( ACC ), glucose transporter-2 ( SLC2A2 ), 3-hydroxy-3-methylglutaryl-CoA reductase ( HMGCR ), and the transcription factor peroxisome proliferator-activated receptor α ( PPARA ) was directed, and a comparison was established between Holstein and F1 Holstein-Gir cows.…”
Section: Strategies To Alleviate Biological Stress During the Transit...mentioning
confidence: 99%
“…However, no significant difference in glucose level was observed within each group during the analysis period. β -Hydroxybutyrate and NEFA concentrations were not different in both genetic groups but showed a high level from prepartum to d 6 and 21 postpartum [ 87 ]. The altered expressions of these different genes in liver are linked with metabolic stress in transition dairy cows.…”
Section: Strategies To Alleviate Biological Stress During the Transit...mentioning
confidence: 99%
“…Crossbreeding in dairy cattle serves mainly for the improvement of functional traits and milk composition of Holstein herds [1][2][3][4][5][6] or uses beef-breed sires over dairy cows to increase income from sales of the beef-cross-dairy calves born on the dairy farm [7]. The majority of these studies, however, report only the results of the first crossbreeding generation (F1) in comparison with the purebred line(s), such as e.g., [8,9] for Holstein-Jersey, or [10] for Holstein-Montbeliarde and Holstein-Viking Red, [11] for Holstein-Gir, or [12] for Holstein-Simmental cows. Only the F1 can reach the maximum heterosis effect, which might improve the performance for most trait complexes, e.g., productivity, efficiency, reproduction, and/or vitality of the F1 offspring by surpassing the average of the parental lines [13].…”
Section: Introductionmentioning
confidence: 99%
“…There was little difference in the abundance of PEPCK mRNA between −7 d and 14 d relative to calving. Laguna et al [34] reported similar findings for the mRNA abundance of cytosolic PEPCK in dairy cows during the transition period. These results indicate that PC is more susceptible to EB than PEPCK, and that PEPCK is a more important rate-limiting enzyme involved in glucose production than PC.…”
Section: Discussionmentioning
confidence: 54%